Family Intervention in The Problem of Maternal Death: A Case Study of Pregnant Women in Mbojo, Bima, West Nusa Tenggara - Atik Triratnawati; Anis Izdiha (Humaniora, 2018)
In 2015, the maternal mortality rate in Bima was recorded as 3 cases per 1,000 births, equivalent to 300 maternal deaths per 100,000 births. Although this number is low, it is much higher than the zero mortality rate set by the Sustainable Development Goals. This study discusses the family and community aspects of the maternal health framework, reading the gendered symbolic violence that affect maternal health in Jatibaru Village, Asakota, Bima, West Nusa Tenggara. Data was collected using an ethnographic approach, with techniques including Focus Group Discussions, participatory observation, interviews, and document study. The existence of gender inequities in the family can cause problems when women attempt to access healthcare. Furthermore, families and communities exert control over pregnant women, directing their behavior and attempts to access healthcare according to local customs and traditions. As such attitudes and behaviors are part of the digestive process of knowledge and experience, women often accept and do what is recommended by their families and communities. This social reality of maternal health thus becomes part of gender inequality in society.